2020
DOI: 10.3390/plants9080933
|View full text |Cite
|
Sign up to set email alerts
|

Shading Affects Yield, Elemental Composition and Antioxidants of Perennial Wall Rocket Crops Grown from Spring to Summer in Southern Italy

Abstract: Shading nets have been increasingly drawing research interest, as they allow us to improve the environmental conditions for greenhouse-grown crops. The effects of two shading nets (50% and 79% shading degree), plus an unshaded control, on yield, mineral composition and antioxidants of perennial wall rocket (Diplotaxis tenuifolia L.-D.C.) grown under tunnels in southern Italy were determined. The shading application resulted in a yield decrease, compared to the unshaded control, except for the highest productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 70 publications
2
6
0
Order By: Relevance
“…There was no significant influence of shading treatments on the leaf mineral contents (i.e., N, P, K, and Ca) of sweet pepper in this experiment (Table 3). This result agrees with that of Caruso et al (2020), who found that the mineral composition of the shaded perennial wall rocket (Diplotaxis tenuifolia) plants was not significantly different from that of the unshaded crops.…”
Section: Effects Of Colored Shadingsupporting
confidence: 92%
See 1 more Smart Citation
“…There was no significant influence of shading treatments on the leaf mineral contents (i.e., N, P, K, and Ca) of sweet pepper in this experiment (Table 3). This result agrees with that of Caruso et al (2020), who found that the mineral composition of the shaded perennial wall rocket (Diplotaxis tenuifolia) plants was not significantly different from that of the unshaded crops.…”
Section: Effects Of Colored Shadingsupporting
confidence: 92%
“…Under such stressful environments, there is an ever-increasing need to improve and understand environmental controls that can enhance plant growth and production (Ili c et al, 2017). The extreme variabilities in air temperatures and solar radiation during the crop growing seasons have been shown to be vital to plant growth and yield (Caruso et al, 2020). However, only solar radiation intercepted by the crop can contribute to photosynthesis (D ıaz-P erez, 2013) improved as shading levels were increased (Kittas et al, 2012).…”
mentioning
confidence: 99%
“…In addition, nitrogen assimilation and accumulation are strongly linked to nitrate reductase activity, a process strongly affected by light [13]. The effects of light and fertilization are opposite; the nitrate content in green plant tissues has a direct relation with N fertilization and inverse with light [4,5,11,[14][15][16][17][18]. Since the light intensity varies during the season, the nitrate content also shows a seasonal behavior.…”
Section: Introductionmentioning
confidence: 99%
“…We again used E. sativa and D. tenuifolia for consistency, and because these species differ in the content of health-promoting phytochemicals, have a wide distribution, and are of increasing importance after the circulation of the ready-to-use salads in the vegetable retail markets ( Heimler et al, 2007 ; Caruso et al, 2020 ). The species E. sativa , in particular, has been artificially selected and this may have led to some biochemical and physiological differences with D. tenuifolia .…”
Section: Introductionmentioning
confidence: 99%